Permafrost investigations in the MacKenzie Delta - Brown, R. J. E. (1958)
In 1953 the Canadian government decided that a new townsite should be found for Aklavik. The poor soils for building dictated that the new site be off the Mackenzie Delta. The ground conditions encountered at the various potential townsite areas were prime factors in determining their suitability as building sites. Sixteen drill holes were made, each approximately 30 ft. deep, and 150 samples were taken. The gravel soils, with relatively low ice content, were one of the deciding factors in the selectione of the new townsite. En 1953, le gouvernement canadien décidait de trouver un nouveau site pour Aklavik. Les sols du delta du Mackenzie n'étant pas appropriés à la construction, le nouveau site devait se situer à l'extérieur de cette zone. les conditions du sol des différents sites possibles constituaient le principal facteur de choix. Seize forages ont été réalisés à une profondeur d'environ 30 pieds et 150 é chantillons ont été prélevés. La présence d'un sol graveleux avec une teneur en glace relativement faible a constitué l'un des facteurs décisifs pour le choix du nouveau site. Peer reviewed: No NRC publication: Yes